Relevance of Educational Research: An Ontological Conceptualization. (August 2021) - Akkerman, Sanne F.; Bakker, Arthur; Penuel, William R.
Educational research is repeatedly confronted with the question of its relevance. Current interpretations of relevance narrowly focus on outcomes and impact of research. In this essay, we propose an alternative, ontological conceptualization of relevance, arguing that more is at stake than outcomes and impact. We characterize the ontology of education and learning in terms of people's meaningful movements in an always changing world and propose that relevance of educational research resides in what we call "ontological synchronization"—continuous attunement to what is happening and matters at hand, and what future is being generated, including what values and judgments researchers themselves perpetuate in society. Such synchronization, we conclude, hinges on a disciplinary and ethical commitment to principles of actuality and generativity. We discuss what such conceptualization of relevance implies for educational research.